2020
DOI: 10.1126/scitranslmed.aaz1803
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic markers associated with metformin response and intolerance in drug-naïve patients with type 2 diabetes

Abstract: Metformin is the first-line pharmacotherapy for managing type 2 diabetes (T2D). However, many patients with T2D do not respond to or tolerate metformin well. Currently, there are no phenotypes that successfully predict glycemic response to, or tolerance of, metformin. We explored whether blood-based epigenetic markers could discriminate metformin response and tolerance by analyzing genome-wide DNA methylation in drug-naïve patients with T2D at the time of their diagnosis. DNA methylation of 11 and 4 sites diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 71 publications
(103 reference statements)
0
28
0
2
Order By: Relevance
“…These biomarkers are only useful after the disease onset. In addition, CpG methylation markers may represent a powerful tool for the early detection of T2D complications [68,69] and for the stratification of drug-naïve patients with T2D in responders/non-responders to glycemic-lowering mediations [122,123].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These biomarkers are only useful after the disease onset. In addition, CpG methylation markers may represent a powerful tool for the early detection of T2D complications [68,69] and for the stratification of drug-naïve patients with T2D in responders/non-responders to glycemic-lowering mediations [122,123].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, García-Calzón et al investigated the hypothesis that blood-based epigenetic markers may discriminate response and tolerance to metformin therapy in T2D patients [122]. In this effort, genome-wide DNA methylation was analyzed in three different cohorts of drug-naïve patients with T2D at the time of diagnosis.…”
Section: Dna Methylation and Type 2 Diabetes: Blood Cellsmentioning
confidence: 99%
“…The authors remarked that the methylation pattern of these sites in blood met the methylation pattern in adipose tissue, suggesting that the identified epigenetic changes might also regard metabolically relevant tissues for type 2 diabetes. Finally, the authors showed that silencing five genes annotated to the identified sites significantly altered the expression of metformin transporter genes and genes coding for gluconeogenetic enzymes in cultured hepatocytes, further supporting a link to the pharmacology of metformin [ 122 ].…”
Section: Molecular Mechanisms Underlying Metformin Actionsmentioning
confidence: 99%
“…Apart from directly targeting a number of metabolic enzymes and transporters, such as glucose transporters GLUT1 and GLUT4, glycogen synthase (GS), acetyl-CoA carboxylase (ACC), and hydroxymethylglutaryl-CoA reductase (HMGCR), AMPK also regulates cell metabolism at the transcriptional level by phosphorylating sterol regulatory element-binding protein 1 (SREBP1), ChREBP, PGC-1α, and transcription factor forkhead box O3 (FOXO3) [ 7 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , …”
Section: Cell Signaling and The Anticancer Activity Of Metforminmentioning
confidence: 99%
“…The A/A genotype carriers had lower methylation (83.6 AE 2.3%) compared to carriers of the G/G (85.3 AE 1.9%, P = 0.002) and G/A (85 AE 1.8%, P = 0.006) genotypes in 132 participants from the discovery and replication cohorts. Lower methylation of this CpG site was associated with a better glycemic response to metformin (Table 2) [129]. In previous work from the same group, they assessed the DNA methylation in OCT1 encoded by SLC22A1, OCT3 encoded by SLC22A3, and MATE1 encoded by SLC47A1 liver biopsies from gastric bypass surgery.…”
Section: Epigeneticsmentioning
confidence: 99%